Food habits of flatfishes in Estancia, Iloilo - Andalecio, Merlina Nabuya (1995.)
Flatfishes were sampled monthly from commercial trawlers in Estancia, Iloilo over one year (July 1992 to June 1993). Nine species were examined for food habits. Sample sizes of these species ranged from 6 to 183, total lengths from 8 to 49 cm and body weights from 3 to 783 grams. Stomach contents were examined and the importance of prey items in the diet was assessed by an index of relative importance (IRI) combining measures of frequency of occurence, number, and weight of prey. Pseudorhombus arsius, P. Malayanus, Cynoglossus puncticeps and Pardachirus pavoninus preyed largely on fishes particularly Saurida sp. Crustaceans such as crabs, copepods, and penaeids were the most important prey in the diets of Pseudorhombus javanicus, Cynoglossus bilineatus. synaptura mulleri and Synaptura zebra.Octopus sp. was the most important prey of pseudorhombus dupliciocellatus. Only P. arsius, P. malayanus and S. mulleri were used to determine whether food habits change with size and sex among flatfishes since they all occured at particular time of the year in sufficient numbers. Kruskal-Wallis test shows no significant difference (p>0.05) in their diets between lenght groups (<22 and >22 cm) and between sex. synaptura mulleri had the most varied rey composition (highest diversity H and widest resource breadth B) of all flatfishes examined. Seven principal prey types wee important (IRI>100) in the diets of S. mulleri thus, the high B Value but low dominance d value. Index of similarity (S) and Hierarchical cluster Analysis were used to measure dietary overlap between flatfishes species. Diet overlap based on the number of common prey were high between P.arsius and P. malayanus (S=0.74), between P. malayanus and S. mulleri (S=0.65) and between P. malayanus and S. zebra (S=0.65). similarity of diet was moderate between S. mulleri and s. zebra (S=0.60) and between P. arsius and S. mulleri (S=0.58). Synaptura mulleri consumed the most number of prey. Hierarchical cluster analysis show that P. arsius, P. malayanus, S. mulleri and S. zebra are grouped together while P. javanicus, C. bilineatus and C. puncticeps belong to another group.
Thesis -( M. S. Aquaculture) - Graduate Faculty, University of the Philippines in the Visayas, May 1995.
Keywords: Flatfishes; Food habits; Estancia